Financing Diversification and Profitability of Islamic Banking in Indonesia - Iin Emy Prastiwi; Anik Anik (ITB AAS INDONESIA, 2021)
This study aims to determine the effect of Islamic bank financing diversification based on economic sectors and based on the type of use on profitability. This study uses financing data for Islamic Banks and Islamic Business Units in 2014-2018. The data in this study are the times series data. Data analyzed by used multiple linear regression analyses. This research provides that results that the HHI of diversification of Islamic bank financing based on the economic sector is positively related to increasing the profitability of Islamic banks. It means diversification of financing based on high economic sectors, has an impact on reducing the profitability of Islamic banks in Indonesia. While the HHI of diversification of financing by type of use give a significant influence in increasing the profitability of Islamic banks in a negative direction. If Islamic banking only focuses on channeling financing to the consumption sector, it can have an impact on decreasing profitability. So that Islamic banking needs to equalize the distribution of consumption to the working capital and investment sectors. The results of this study are interesting because it can be used as a reference for Islamic banking in determining the policy of diversification of financing to obtain high profitability with low risk.